Uma proposição de gamificação em sistemas m-Healt para o engajamento dos usuários - Cechetti, Nathália Pinto (2018)
To increasingly engage people on the usage of mobile applications through motivation, gamificationemerges, incorporating game elements in non-game context. The lack of engagement during apatient’s treatment is a regular concern among health professionals, who have been adopting technology as a motivational factor. In this context, this study presents a gamification proposition that aims to promote engagement in user’s treatment with the use of e-Health systems. The proposition considered three key factors: design techniques, system context and the end user. The method is composed by seven stages: inspection and analysis of system requirements and its functionalities,mapping of the target audience characteristics, identification of interaction flows, gamification analysis applied in similar systems, selection of gamification elements, prototyping and development, and, finally, evaluation. The development stage resulted in two versions of the eLifeStyle App, one with the game elements gathered from the previous stages, and one without these elements. The developed application is part of the eLifeStyle platform. The app has eight indicators that help the hypertensive patient to self monitor their health care, which may be followed and assisted by a health professional. At the evaluation stage, 14 hypertensive patients were invited, including five patients undergoing treatment for arterial hypertension, followed by a cardiologist at the Passo Fundo City Hospital; one patient undergoing treatment with a cardiologist at Hospital Santo Antônio of Tapejara; and eight patients who were not assisted by health professionals during the testing period. Participants were divided into four groups to verify if the inclusion of gamification would promote greater engagement in health care, as it follows: CGCA - gamified app and health monitoring with a professional; CGSA - gamified app without monitoring; SGCA - non-gamified app and health monitoring and SGSA - non-gamified app and no health monitoring. Data collection included: engagement questionnaire, technology acceptance questionnaire (TAM), system logs and participants feedback. Results showed gamification favored the engagement, stimulating intrinsic motivation in the participants. In addition, groups assisted by health professionals spent more time with the app, and were motivated in maintaining the control of their health. As conclusion, gamification proved to be effective for this context, since it did not add complexity to the application and promoted the desired engagement results.